The alternative uses of disused dairy factories in Taranaki : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University - O'Donnell, Christine Anne (Massey University, 1983)
Small local dairy factories have long been a part of New Zealand's dairying heritage. No longer profitable in their original use, subsequent redundancy and abandonment has seen the appearance of the "disused dairy factory" in the rural landscape. In disuse these buildings find their greatest asset for potential reuse. As existing capital stock, these disused dairy factories manifest potential opportunities for enterprises other than dairying, to establish alternative uses. As a product of the past, the phenomenon of dairy factory reuse represents a change in use to meet the demands of the present. The extent to which this has been achieved, and how this pattern can be explained, evidences the interaction of past and present forces in effecting a potential future for these buildings.
Keywords: Dairy plants; Factories